THE EFFECT OF INVESTMENT KNOWLEDGE ON STUDENT'S INTEREST IN INVESTING SHARIA SHARE (An-Nisbah: Jurnal Ekonomi Syariah, 2022)
Investment can be interpreted as an activity to invest in both money and objects in an object with the aim of obtaining profits over a certain period. Investment decisions are a very important decision in investing, where in order to get a profit we have to deal with risk, therefore investors must evaluate the relationship between return and risk. This type of research is associative. The data used is primary data obtained through the dissemination of questionnaires to 264 student respondents of the Sharia Economic Law study program of the Faculty of Sharia and legal sciences UIN SATU Tulungagung. The sampling method used by researchers in each study program is proportionate stratified random sampling. The results show that the coefficient value of the variable parameters of investment knowledge is 1.61 which means that any increase in the value of knowledge or understanding of investment will increase one's interest. in investing. This means that there is a positive linear relationship between one's knowledge and one's interest in making investments. The higher the knowledge a person knows investing, the higher one's interest in investing. The result of measuring the goodness of the model is to use the value of the coefficient of determination R2 which shows a number of 48.6%. The value can be interpreted that the model is able to explain the actual condition of only 48.6% where the remaining 51.4% of a person's interest in investing is influenced by other variables outside the investment knowledge variable..